Dividends, Investment Opportunities, and Company Performance: The Moderating Role of Corporate Governance - Bunga Triandolla; Antonius Herusetya (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the influence of dividend policy and investment opportunities set on firm performance, with corporate governance as a moderating variable. The study focuses on mining sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Methodology/approach: This study is quantitative approach. Firm performance is proxied by Return on Equity, dividend policy by Dividend Payout Ratio, and IOS by the ratio of capital expenditure to total assets. Corporate governance is assessed through an index comprising 17 indicators aligned with the principles of Good Corporate Governance. Data analysis was conducted using panel data moderation regression with the Generalized Least Squares. Results/findings: The results indicate that dividend policy tends to positively influence ROE, whereas IOS shows no direct significant impact on ROE. Conversely, corporate governance negatively moderates the relationship between dividend policy and ROE, suggesting that stricter corporate governance weakens the positive effect of dividend policy on firm performance. However, corporate governance does not significantly moderate the relationship between IOS and ROE Conclusion: Dividends positively affect ROE; IOS has no direct effect; governance weakens the dividend effect on ROE but does not moderate the IOS–ROE relationship. Limitations: This research was limited to mining companies in Indonesia. Therefore, the results are limited to one industry and cannot be generalized to all companies in Indonesia. Contribution: This study offers practical implications, emphasizing that management of mining companies should carefully design balanced dividend policies, considering their long-term effects and highlighting the importance of effective corporate governance implementation.